A brief review of tribological properties for black phosphorus - Fanfan Lv; Wei Wang; Jinjin Li; Yuan Gao; Kuaishe Wang (Friction)
Abstract Black phosphorus (BP) is a new class of two-dimensional (2D) layered material, which shows the unanticipated characteristics in many aspects including electronics, transistors, sensors, energy storage, batteries, photocatalysis, and other applications due to its high charge carrier mobility, tunable direct bandgap, and unique in-plane anisotropic structure. In addition, BP has drawn tremendous attention in the field of tribology due to the low shear strength, the layered structure, and the weak connected force between the layers by van der Waals interaction. In recent years, many significant progresses have been made in experimental studies on BP materials as solid lubricants or lubrication additives. This work offers a review of researching regarding the tribological properties of BP. Moreover, the lubrication mechanisms of BP as the lubrication additive including the formation of the tribo-film, micro-bearing effect, and self-repair performance are also summarized. Finally, the current challenges and prospects of BP material as lubricant are proposed.